2007
DOI: 10.1007/s10661-007-9897-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the impact of landfill on groundwater quality: A case study of the Pirana site in western India

Abstract: In present study focus has been given on estimating quality and toxicity of waste with respect to heavy metals and its impact on groundwater quality, using statistical and empirical relationships between different hydrochemical data, so that easy monitoring may be possible which in turn help the sustainable management of landfill site and municipal solid waste. Samples of solid waste, leachate and groundwater were analyzed to evaluate the impact of leachates on groundwater through the comparison of their hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(64 citation statements)
references
References 19 publications
0
59
4
1
Order By: Relevance
“…The suitability of groundwater resources for irrigation purpose was also studied (Sujatha and Reddy 2003;Sadashivaiah et al 2008;Ramesh and Bhuvana 2012). Several published research studies have employed the use of multivariate statistical analysis in the interpretation of groundwater quality data obtained from various sources (Sundaray 2010;Singh et al, 2008;Uddamari et al 2014;Oketola et al 2013;Molla et al 2015;Arslan 2013;Zhang et al 2014;Majolagbe et al 2016;Markic et al 2015;Razmkhah et al 2010). Scientists have also employed the use of principal component analysis (PCA) to study soil physicochemical properties and its geochemical constituents, identification of heavy metals pollutants in soil, analysis of heavy metals presence in dust and evaluation of influence of seasons on air pollution (Adhikari et al 2003;Ma et al 2016;Satyanarayanan et al 2016;Gergen and Harmanescu 2012;Iwara et al 2014;Lu et al 2010;Burt et al 2014;Benhaddya and Hadjel 2014;Abdul Raheem et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The suitability of groundwater resources for irrigation purpose was also studied (Sujatha and Reddy 2003;Sadashivaiah et al 2008;Ramesh and Bhuvana 2012). Several published research studies have employed the use of multivariate statistical analysis in the interpretation of groundwater quality data obtained from various sources (Sundaray 2010;Singh et al, 2008;Uddamari et al 2014;Oketola et al 2013;Molla et al 2015;Arslan 2013;Zhang et al 2014;Majolagbe et al 2016;Markic et al 2015;Razmkhah et al 2010). Scientists have also employed the use of principal component analysis (PCA) to study soil physicochemical properties and its geochemical constituents, identification of heavy metals pollutants in soil, analysis of heavy metals presence in dust and evaluation of influence of seasons on air pollution (Adhikari et al 2003;Ma et al 2016;Satyanarayanan et al 2016;Gergen and Harmanescu 2012;Iwara et al 2014;Lu et al 2010;Burt et al 2014;Benhaddya and Hadjel 2014;Abdul Raheem et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The leachate commonly contains large amounts of organic matter, ammonium, heavy metals, and chlorinated organic and inorganic salts, which cause a great threat to soil-water environment in the vicinity of a landfill site [16][17][18][19]. The compositions of leachate can be divided into four parts of pollutants: (1) Organic matter, COD (chemical oxygen demand) and TOC (total organic carbon); (2) specific organic compounds; (3) inorganic compounds; and (4) heavy metals [6,11,20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other locations have indicated that MSW landfills can significantly affect the contamination of groundwater with heavy metals: Ahmadabad (Cd-0.003, Pb-0.042 [31]; and Calcutta [32] in India; Ibb City in Jemen [33]; Cartagena in Colombia [34]; Vejen landfill in Denmark [35]; Ano Liosia landfill in Greece [36]; and Zagreb in Croatia [37]. The contents of all analyzed heavy metals (Table 3) in the subsurface soil horizon (0-25 cm and at 25-50 cm) were low, as is commonly observed for farmlands and forest areas in Poland [38].…”
Section: Resultsmentioning
confidence: 99%